Primary renal lymphoma: a rare cause of renal mass in pediatric age group: case report and review of literature - Thakur, Karishma; Wadhwani, Sonam; Ghodawat, Meha; Prakash, Advait; Khare, Abhinav; khaitan, Aditya; Singh, Sangram; Malhotra, Anuj (International Surgery Journal, 2020)
The secondary renal involvement of non-Hodgkin lymphoma is frequently encountered but primary renal lymphoma is extremely rare in children. We hereby present a rare case of primary renal diffuse lymphoma in a 3-year-old girl child who presented with bilateral renal masses. The tumour was initially diagnosed as bilateral Wilms’ tumour but on biopsy, it turned out to be non-Hodgkin’s lymphoma. Primary renal lymphoma is an aggressive tumour with guarded prognosis. There are a variety of diseases which present as renal masses in children amongst which primary renal lymphoma is extremely rare. This article describes the clinical features and diagnostic features of primary renal lymphoma. Our report highlights the importance of keeping this neoplastic condition under consideration while evaluating children with renal mass .In order to distinguish primary renal lymphoma from other renal tumours, the authors have also described the clinical, imaging and pathological features of various other renal tumours prevalent in children.